Evidence of macrophagous teleosaurid crocodylomorphs in the Corallian Group (Oxfordian, Late Jurassic) of the UK - Foffa, Davide; Young, Mark T.; Brusatte, Stephen L. (PeerJ, 2015)
Teleosaurids were a group of semi-aquatic crocodylomorphs with a fossil record that spanned the Jurassic Period. In the UK, abundant specimens are known from the Oxford Clay Formation (OCF, Callovian to lower Oxfordian), but are very rare in the Kimmeridge Clay Formation (KCF, Kimmeridgian to lower Tithonian), despite their abundance in some contemporaneous deposits in continental Europe. Unfortunately, due to the paucity of material from the intermediate ‘Corallian Gap’ (middle to upper Oxfordian), we lack an understanding of how and why teleosaurid taxic abundance and diversity declined from the OCF to the KCF. The recognition of an incomplete teleosaurid lower jaw from the Corallian of Weymouth (Dorset, UK) begins to rectify this. The vertically oriented dentition, blunt tooth apices, intense enamel ornamentation that shifts to an anastomosed pattern apically, and deep reception pits on the dentary unambiguously demonstrates the affinity of this specimen with an unnamed sub-clade of macrophagous/durophagous teleosaurids (‘Steneosaurus’ obtusidens + Machimosaurus). The high symphyseal tooth count allows us to exclude the specimen from M. hugii and M. mosae, but in absence of more diagnostic material we cannot unambiguously assign DORCM G.3939 to a more specific level. Nevertheless, this specimen represents the first mandibular material referable to Teleosauridae from the poorly sampled middle-upper Oxfordian time-span in the UK.
Keywords: Steneosaurus; Machimosaurus; Thalattosuchia; Corallian Gap; Teleosauridae